Recursive Process for Constructing the Refinement Rules of New Combined Subdivision Schemes and Its Extended Form - Rabia Hameed; Ghulam Mustafa; Jiansong Deng; Shafqat Ali (Journal of Mathematics)
In this article, we present a new method to construct a family of 2N+2-point binary subdivision schemes with one tension parameter. The construction of the family of schemes is based on repeated local translation of points by certain displacement vectors. Therefore, refinement rules of the 2N+2-point schemes are recursively obtained from refinement rules of the 2N-point schemes. Thus, we get a new subdivision scheme at each iteration. Moreover, the complexity, polynomial reproduction, and polynomial generation of the schemes are increased by two at each iteration. Furthermore, a family of interproximate subdivision schemes with tension parameters is also introduced which is the extended form of the proposed family of schemes. This family of schemes allows a different tension value for each edge and vertex of the initial control polygon. These schemes generate curves and surfaces such that some initial control points are interpolated and others are approximated.